2021
DOI: 10.15282/ijim.10.1.2021.5982
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study on the implementation of Mahalanobis-Taguchi system and time driven activity-based costing in electronic industry

Abstract: Electrical and electronic industry is one of Malaysia’s leading industries which covers around 24.5% in manufacturing production sector. With a continuous innovation of the Industry, inductor component gets higher demand from customer and it is good if there is a study to convince that those factors are really significant to the production as well. Meanwhile, the current costing being used is difficult to access the complete activities required for each workstation and need separate analysis to measure the un-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Meanwhile, also developed the time equation, capacity cost rate, capacity utilization and unused capacity in the nursery of palm oil plantation and the manager has alternatives of lowering the cost of production by increasing work capacity and reducing waste costs. Kamil, Zaini and Abu (2021) concluded that Mahalanobis-Taguchi system and TDABC are a great tool and feasible to be implemented in the electronic industry. TDABC was discovered by to be in accordance with actual resource utilisation in the identification of overall costs and identified some activities with added value to the operation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, also developed the time equation, capacity cost rate, capacity utilization and unused capacity in the nursery of palm oil plantation and the manager has alternatives of lowering the cost of production by increasing work capacity and reducing waste costs. Kamil, Zaini and Abu (2021) concluded that Mahalanobis-Taguchi system and TDABC are a great tool and feasible to be implemented in the electronic industry. TDABC was discovered by to be in accordance with actual resource utilisation in the identification of overall costs and identified some activities with added value to the operation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kamil et al [37] concluded that MTS is a practical method for classification and optimization in the industry. Kamil et al [38] concluded that MTS and TDABC are great tools and feasible to be implemented in the electronic industry. Saad et al [39] developed an MTS-based graphical user interface to analyze and classify normal and abnormal patients under MFlex service for a better monitoring system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[11] discovered that a positive rise in SNR implies that the system's quality remained acceptable from February (0.1244) to December (0.4432), after unimportant parameters using MTS. [35] found that MTS is advantageous for classification and optimization in industry. [36] found that MTS and TDABC are a great resource that can be easily used in the electronic industry.…”
Section: Introductionmentioning
confidence: 99%
“…[35] found that MTS is advantageous for classification and optimization in industry. [36] found that MTS and TDABC are a great resource that can be easily used in the electronic industry. [37] used the MFlex service to make the tracking system better by creating an MTS-based graphical user interface for analyzing and sorting patients into groups of normal and abnormal variants.…”
Section: Introductionmentioning
confidence: 99%